Problems of compensation for moral damages for violation of labor rights - Оніщенко, Ольга Вікторівна; Гораш, Ірина Степанівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
Statement of the problem. Moral damages is a key issue as labor and civil rights as an important guarantee of the rights and freedoms of citizens. To socio-economic changes that have occurred in our state, the labour legislation was not even such thing as moral damages. At the moment, when in society the priorities are the rights and freedoms of the individual, the emergence of the right provisions about compensation of moral harm are essential. The current legislation of Ukraine does not contain clear and sufficient for its regulation, therefore, moral damages in the labour law remains a debatable question. The main material of the study. The article established that the moral damages is a liability of the employer in labour relations. Institute of compensation of moral (non-property) damage in labour and civil law are significantly different from each other in subject composition. Also, the labor law does not always apply to legal relations arising on the basis of an employment contract, in some cases, the occurrence of certain legal fact leads to the application of the provisions of the Civil code. In the study of this issue revealed that the labour legislation does not regulate the questions connected with compensation of moral harm to the employer by the employee, which entails one of the many consequences of inequality of the parties in these legal relations. Analysis of judicial practice has allowed to establish that clearly defined the size of indemnification of moral harm does not exist, so the court in its discretion determines the amount of such compensation. One of the mandatory conditions of the legal responsibility of the employer there is a labour offence. Conclusions. The result of this research is that the Institute of compensation for moral (non-property) damage in labour law is characterized by its individual specifics. It is to the subject the composition of these relations, and to define certain rights and obligations of relevant actors – the employee and the employer.